ANALISIS KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN PAJAK DAERAH PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KABUPATEN MINAHASA SELATAN - Anugrahi, Rachelyta; Manossoh, Hendrik; Tangkuman, Steven J. (Universitas Sam Ratulangi, 2018)
Restaurant Tax is one of the types of Regional Taxes. Regional Tax is a compulsory levy paid by a resident in a region to the local government of that place which will be used for the benefit of local government and public interest. The objective of this research is to know the contribution of Restaurant Tax to local tax revenue. This research uses descriptive qualitative method. The result of research shows that the contribution given by the improvement from 2014 is 5.13%, and the next year 2015 is 8.74%, then 2016 is 11.66%, until 2017 is get 12.58%. The effectiveness level of restaurant tax has fluctuated from 2014 to 2017.Keywords: Contribution, Restaurant Tax, local Tax, Effectiveness